Understanding Hungarian recreational forest landscape development towards forest conservation - Hussein, Mohd. Kher (Academy of Business & Scientific Research, 2014)
Recreational Forest or Park Forest in Hungary was under the control of State Forest Management Corporations. Their establishment was principally to serve social and public welfare interests as well as for conservation purposes. As a consequence, many facilities and activities being implemented to meet those development principles which indirectly changing the existing forest landscapes. Now, there are has two combination of landscapes in Hungarian recreational forest which are natural landscape and human made landscape elements. However, the developments are within the framework of welfareoriented forestry. Therefore, it is necessary for the public to understand the landscape development practices in this park. Aim of this study is to get a better understanding of recreational forest landscape development in Hungary towards forest conservation. Objective of the study is to gain an overview of recreational forest landscape expansion and management practice in Hungary through the case of Pilis Park Forestry Company. Today, recreational forest in Hungary covered around 50 thousand hectares since the campaign for park forests in the 1970s. Clearly, the effort taken by the government to keep and conserve country forest is successful where the total forested area is increasing.